The relationship between construction and environment : The perspectives of town planning system - Asmawi, M. Zainora (International Islamic University Malaysia, 2010)

(untitled)
Environment forms the basis upon which all human activities such as physical, social and economy take place. Malaysia is a nation that is blessed with the beauty of nature and at the same time advanced in terms of infrastructural development. Environmental resources are vital components of the environment that include land, vegetal resource, water bodies, atmosphere, flora and fauna. Nowadays, due to high rate of urbanisation, rapid population growth, and rapid economic growth led to greater need of space for operation, which subsequently forced the construction industries to meet this demand. This gives rise to various forms of environmental degradations which lead to disruption of environmental equilibrium. The study assesses the effects of construction industries on the environment in the perspectives of town planning. Town planning is an approach used to identify the relationship between construction activities and environmental resources with the aid of some tools such as Development Proposal Report, development control and planning permission among others. The study finds out that construction industry has grown to 17.4% during the period of 1996-2000, which is the peak period and is due to mega projects that mostly took place in the Federal Capital and the central part of Peninsular Malaysia. The methodology employed in this study is based on the available data derived from the secondary sources of information. It also aims at suggesting ways of achieving sustainable construction activities, so that our natural earth will not be harmed, destroyed or degraded